Research on Visualization Techniques Based on Chinese Texts - Hai Yuan; Kang Chen; Caixia Tao; Chong Chen (Dianxin kexue)
The text visualization process was introduced at first, including information collection, preprocessing, visual presentation and interactive functions. Then based on the analysis of various Chinese text visualization tools, the visualization technology areas such as multi-based tag cloud, tree map, association and time sequences were researched. At last, the advantages and disadvantages of these techniques were compared from a few aspects and the various technologies applicable to the scene were pointed out. Text visualization can help users to better deal with the growing text information to improve the efficiency of data visualization and converted into efficiency benefits.